PENGARUH NPF, FDR, BOPO TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM SYARIAH - LEMIYANA, LEMIYANA LEMIYANA; LITRIANI, ERDAH ERDAH (I-Economics, 2016)
This research using causal assosiative method. The data using time series and cross section period 2011 – 2015 with SPSS application. The population are Bank Umum Syariah (BUS) in Indonesia which is registered in Bank Indonesia directory period 2011- 2015 that is 12 Bank Syariah. The result showed that Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR), has no influence to Return On Asset (ROA). While Operational Cost variable to Operational Revenue (BOPO) has negative influence to Return On Asset (ROA). Capital Adequacy Ratio (CAR) has no negative influence significantly between CAR to ROA. Inflation and Exchange rate variable has no influence to ROA. NPF, FDR, BOPO, CAR, Inflation, and Exchange rate variables has no influence significantly to ROA. The contribution of all independent variables (NPF, FDR, BOPO, CAR, Inflation, and Exchange rate) to ROA is 71,9% and the rest of value 28,1% can be describe by other variable outside this research model.Key word: NPF, FDR, BOPO, ROA, BUS (Bank Umum Syariah)